2004
DOI: 10.1038/sj.onc.1207510
|View full text |Cite
|
Sign up to set email alerts
|

RARβ2 is a candidate tumor suppressor gene in myelofibrosis with myeloid metaplasia

Abstract: Myelofibrosis with myeloid metaplasia (MMM) is a clonal stem-cell disorder that leads to ineffective hematopoiesis, bone marrow fibrosis, and extramedullary hematopoiesis. The molecular mechanisms underlying the development of this myeloproliferative syndrome are currently unknown. In order to identify tumor suppressor genes that may be involved in the disease process, we performed an analysis for loss of heterozygosity (LOH) in CD34 þ cells from 29 patients with MMM. We observed a frequency of allelic loss on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
(35 reference statements)
1
26
1
Order By: Relevance
“…A substantial amount of evidence has been generated which indicates that these somatic mutations play a significant role in the pathobiology of the MPDs. In addition to these genetic mechanisms, a growing number of investigators have provided data which indicate that epigenetic mechanisms silence genes that impede cellular proliferation or movement in IM (19)(20)(21). Rossi et al (39) have reported aberrant methylation of a variety of negative regulators of JAK2 activation/phosphorylation, including SHP-1, SOCS-1, and SOCS-3, which have been observed in patients with both JAK2V617F-positive or JAK2V617F-negative IM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial amount of evidence has been generated which indicates that these somatic mutations play a significant role in the pathobiology of the MPDs. In addition to these genetic mechanisms, a growing number of investigators have provided data which indicate that epigenetic mechanisms silence genes that impede cellular proliferation or movement in IM (19)(20)(21). Rossi et al (39) have reported aberrant methylation of a variety of negative regulators of JAK2 activation/phosphorylation, including SHP-1, SOCS-1, and SOCS-3, which have been observed in patients with both JAK2V617F-positive or JAK2V617F-negative IM.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that CXCR4 expression was down-regulated in the CD34 + cells of patients with IM; this abnormality was thought to contribute to the constitutive mobilization of hematopoietic stem and progenitor cells that occurs in patients with IM (14,18). The malignant phenotype in IM likely results from a combination of genetic abnormalities and epigenetic modifications leading to the dysregulation of critical genes that contribute to cell proliferation, differentiation, and cell death (2)(3)(4)(5)(6)(7)(19)(20)(21). Methylation of cytosine residues in the promoter region as well transcriptional inhibitory complexes including histone deacetylases (HDAC) play a role in the transcriptional silencing of genes in a variety of human cancers (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…CpG island methylation has been infrequently assessed in patients with a MPD. Jones et al 44 detected methylation of the retinoic acid receptor-β gene (RARB) in 89% (16/18) of IMF patients and also showed reduced expression in CD34 + cells. However, Jost et al 45 failed to detect methylation of RARB in any of 23 MF patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Epigenetic modifications leading to the dysregulation of critical genes that contribute to cell proliferation, differentiation, cell death, and trafficking have also been thought to play a role in the origins of PMF. [8][9] Mutations in TET2, for instance, might contribute to the origins of PMF by altering chromatin structure. TET1 affects the conversion of 5-methylcytosine to 5-hydroxymethylcytosine and therefore influences epigenetic regulation of transcription.…”
Section: Introductionmentioning
confidence: 99%